A history of nationalism in modern Japan : placing the people - Doak, Kevin Michael (Handbuch der Orientalistik. Japan, 2007)
Provides an overview of the debates over Japanese national identity and nationalism from the middle of the nineteenth century onwards. This work presents Japanese nationalism as a contestory practice that positions "the people" as what the nation is and what nationalism seeks to achieve. It also explores sites where this practice has been intense.